Medico-Legal System in Sexual Assault Cases in India - Yuvraj Dilip Patil (Journal of Krishna Institute of Medical Sciences University)
Sexual assault is a heinous crime. Man com-mits the act to fulfill his sexual urge, to showhis masculinity, to get control of the victim, totake revenge and various other reasons, out ofabnormal mind, out of ignorance of the law ofthe land or out of opportunity. The mental traumasuffered by the victim may linger till end of herlife [1].Women who wish to pursue a justice againsttheir assailant are usually examined by a doc-tor or in most cases a state-employed districtsurgeon, and obtain a report of their injuries.Expert medical evidence is widely used in sexualassault cases, but its contribution to theprogress of legal cases is unclear.The objectives of the paper are -1. To study the legislative provisions re-lating to medical examination in SexualAssault cases.2. To assess the impact of medico legal evi-dence in sexual assault cases.3. To make suggestions.